2011
DOI: 10.1007/s10457-011-9463-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for important genetic differentiation between provenances of Parkia biglobosa from the Sudano-Sahelian zone of West Africa

Abstract: Parkia biglobosa is a traditional economic tree legume of considerable multipurpose importance in the sudano-sahelian region in Africa. The species grows in multiple climatic zones with precipitation ranging from 600 to 2,500 mm a year and its natural distribution extends from Senegal and Guinea in West Africa to Uganda in Central Africa. In the present paper, a range wide sample of 25 provenances of P. biglobosa was tested in Burkina Faso, West Africa at two sites; Gonse (latitude 12°25 0 N; longitude 1°20 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Northeast India exhibited a varied agroclimatic zones having very high rainfall and potentially lesser evapotranspiration like Shillong (Perhumid) to a place having lesser rainfall with high aridity and temperature like Jiribam (Arid). Similar climatic amplitudes was reported for Parkia biglobosa in Sudano-Sahelian zone of West Africa (Quedraogo et al, 2012).…”
Section: B Effect Of Agroclimatic Zones On Seedsupporting
confidence: 85%
“…Northeast India exhibited a varied agroclimatic zones having very high rainfall and potentially lesser evapotranspiration like Shillong (Perhumid) to a place having lesser rainfall with high aridity and temperature like Jiribam (Arid). Similar climatic amplitudes was reported for Parkia biglobosa in Sudano-Sahelian zone of West Africa (Quedraogo et al, 2012).…”
Section: B Effect Of Agroclimatic Zones On Seedsupporting
confidence: 85%
“…Although significant interactions between different water regimes and provenances were found, it was not possible, based on growth traits including fresh and dry weight or shoot-to-root dry weight ratios, to clearly separate provenances according to their geographic origin or to climatic parameters. A substantial genetic differentiation in growth traits and survival rate, based on the coefficient of variation among 25 provenances (13-yr old) from West and Central Africa was reported (Ouedraogo et al, 2012). Relationships between some geographical parameters (longitude, latitude) and traits (height, basal area and survival) were significant.…”
Section: Quantitative Genetic Variationmentioning
confidence: 96%
“…A high mortality rate was recorded even for local provenances, showing potential limitations in using the species for plantation. Furthermore, an assessment of these provenance trials 13 years after their establishment showed mean survival rates of 35 % and 61 % at Gonse and Dinderesso, respectively (Ouedraogo et al, 2012). Two local provenances had lower survival rates (29 % and 57 %, respectively) compared to the mean performance of all provenances in the two trials (Ouedraogo et al, 2012).…”
Section: Marker-based Genetic Diversity and New Analysis Of Allozyme mentioning
confidence: 98%
“…Based on two older field trials, Ouedraogo et al (2011) show that P. biglobosa provenances differ in survival and growth. Performance of the provenances correlated with latitude, longitude and precipitation at their origin.…”
Section: Variation In Fruit Quality and Quantitymentioning
confidence: 99%